The Impact of the Real Estate Tax in Maximizing Tax Revenues : applied research (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Tax revenues are considered one of the important sources of public revenues for the state as one of the tributaries that finance the public treasury to implement development plans. Real estate taxes are one of the sources of obtaining tax revenues in the state, as it follows that there are a number of factors that affect these revenues, which requires the development of necessary solutions and recommendations to address the resulting effects. Accordingly, this research sheds light on tax revenues in general and real estate tax revenues in particular to indicate the extent of their contribution to the total tax proceeds, as the tax proceeds of the real estate tax were analyzed into the total tax proceeds for the years (2017-2021). A number of conclusions were reached, the most important of which is the weak contribution of real estate tax to the total tax proceeds, as it ranged from (1.78-280) for the above years. The research recommended the tax proceeds.